The Effect of Brands and Advertising on the Purchase of Pepsodent Toothpaste Products in Pagar Alam City - Ruaman Yudianto (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect of brands and advertisements on the purchase of Pepsodent toothpaste products in the community of Sukorejo Village, North Pagar Alam District, Pagar Alam City. In this study using the independent variable brand (X1), and advertising variable (X2). Brand and advertising variables as independent variables and purchase (Y) as dependent variable. This research uses Multiple Linear Regression method. The sample used in this study amounted to 100 respondents who are consumers of Pepsodent toothpaste products in Sukorejo Village, North Pagar Alam District, Pagar Alam City. The data obtained is primary data which is the result of respondents' answers to the distributed questionnaires. Based on the research conducted, the results showed that there was a simultaneous influence of brand variables (X1) and advertising (X2) on the purchase (Y) of Pepsodent toothpaste products in Sukorejo Village, North Pagar Alam District, Pagar Alam City. The results of this study also show that brand and advertising variables partially have a significant effect on the purchase of Pepsodent toothpaste products in Sukorejo Village, North Pagar Alam District, Pagar Alam City. In the determination test there is an effect of 27.mf% of the independent variables (brands and advertising) on ​​the dependent variable (purchases). While the remaining 72.2% is influenced by other variables outside of this study.